The perceived impact of industrial supplier-manufacturer relationship on strategic outsourcing success / Noor Aziani Harun - Harun, Noor Aziani (2012)
The purpose of the current study was to examine the antecedent to supplier-manufacturer relationship and relationship between relational-oriented exchange and outsourcing success of supplier-manufacturer relationship within Malaysia. There are three dimensions of antecedents of a relational-oriented exchange which are dependence, trust, and communication behavior that has been measured the impact on strategic relationship between relational-oriented exchange and outsourcing success of supplier-manufacturer relationship within Malaysia. This study used the partial least squares (PLS) and structural equation modeling (SEM) tool to test the hypotheses. The data was gathered from a postal survey of 865 electrical & electronics sub-sector, of which 216 respondents participated in this study. The result indicated that the antecedent was positively related to relational-oriented exchange and relational-oriented exchange was positively related to the outsourcing success. Implications of the findings are further elaborated